ANALISIS KEEFEKTIFAN PELATIHAN TERHADAP KOMPETENSI KEPRIBADIAN GURU DI SD NEGERI TUBUNAUS - Aoetpah, Richard Leonando (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2022)
The purpose of this research is to analyze the effectiveness of training on the personality competencies of teachers at SD Negeri Tubunaus. This study uses qualitative research methods. The method used for data collection is interview technique. The data analysis technique used is qualitative data analysis, the results of this research are From the indicators of teacher personality competence, it shows that education and training are effective for the development of teacher personality competencies in schools, teachers show more personality which is shown through indicators of a teacher's personality, including being patient, disciplined, wise, having a leadership spirit and being able to self-assess. of work performance. There are recommendations for training participants, in this case teachers, to see all the needs of the training so that training can be more effective for the personality of the teacher. And for other research to see from the side of the teacher's social competence.